(untitled) (Third Sector Social Economic Review, 2020)
The purpose of this research is to determine the role of cultural dimensions in entrepreneurship tendencies of university students. The research was carried out using a quantitative research design. 200 people who were trained at the Faculty of Economics and Administrative Sciences of Aksaray University and received entrepreneurship education were collected by using the questionnaire method with easy sampling method. The data obtained was analyzed through the SPSS program and descriptive statistics were analyzed using the Anova, factor, correlation and regression analysis method. According to the findings obtained from the research, it was determined that Aksaray University Faculty of Economics and Administrative Sciences students’ cultural dimensions of avoiding uncertainty, power distance, masculinity-femininity, checkpoints and individualism-socialism were influential.